2017
DOI: 10.4155/fmc-2016-0207
|View full text |Cite
|
Sign up to set email alerts
|

Pseudokinases: Update on Their Functions and Evaluation as New Drug Targets

Abstract: The pseudokinase complement of the human kinase superfamily consists of approximately 60 signaling proteins, which lacks one or more of the amino acids typically required to correctly align ATP and metal ions, and phosphorylate protein substrates. Recent studies in the pseudokinase field have begun to expose the biological relevance of pseudokinases, which are now thought to perform a diverse range of physiological roles and are connected to a multitude of human diseases, including cancer. In this review, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 184 publications
(233 reference statements)
1
69
0
Order By: Relevance
“…In contrast, among 50 human pseudokinases, 33 contain a residue other than Asp at the equivalent position. Therefore, missing the Asp residue is considered a hallmark of pseudokinases, even though some pseudokinases were discovered to possess significant kinase catalytic activity . Whether Asp can be replaced by any other residue has not been fully tested in any kinase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, among 50 human pseudokinases, 33 contain a residue other than Asp at the equivalent position. Therefore, missing the Asp residue is considered a hallmark of pseudokinases, even though some pseudokinases were discovered to possess significant kinase catalytic activity . Whether Asp can be replaced by any other residue has not been fully tested in any kinase.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, missing the Asp residue is considered a hallmark of pseudokinases, even though some pseudokinases were discovered to possess significant kinase catalytic activity. [35][36][37][38] Whether Asp can be replaced by any other residue has not been fully tested in any kinase. The screening of an Asp386 mutant library indicated that no other residue was able to replace Asp386 to allow significant kinase activity in Src (>0.2% of wild-type).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the HER3 pseudokinase, although reported to have low catalytic activity, serves mostly as an allosteric activator for other members of the EGFR family of receptor kinases (Jura et al, 2009; Shi et al, 2010). These studies have highlighted the importance of pseudokinases in human biology and their diverse signaling functions make them attractive drug targets (Bailey et al, 2015; Byrne et al, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…This work shows that the various speculations about the biological role(s) of human and amniote PANK4s are not due to PANK activity as previously believed. HsPANK4 may have an alternative function(s) and should be considered a pseudoenzyme …”
Section: Introductionmentioning
confidence: 99%
“…HsPANK4 may have an alternative function(s) and should be considered a pseudoenzyme. [21][22][23][24]…”
Section: Introductionmentioning
confidence: 99%